"Prayer is the answer": Apocalypticism, Our Lady, and Catholic Identity. Issue 1 (18th June 2016) - Krebs, Jill
Abstract: Apocalyptic beliefs are common in modern Marian apparitions and represent an important area of tension between believers and skeptics—tension that in part determines the official Church stance toward, as well as popularity and longevity of, the apparition. Apocalypticism therefore is an important component of Catholic identity for many Marian devotees. Drawing from a case study of a modern apparition site in rural Emmitsburg, Maryland, I argue that apocalyptic beliefs shape Catholic identity by framing social and religious changes as evidence of coming chastisement; galvanize action among believers, who both prepare for and attempt to avert apocalypse; and validate the Catholic identity of those individuals marginalized within their communities because of those same apocalyptic beliefs. Using Christian Smith's subcultural identity theory of religious persistence and strength, as well as literature on apparitional movements, I describe the dynamics of apocalyptic belief in modern Marian apparitions, explore how the tension engendered by apocalypticism promotes strong identity through symbolic boundary marking, and argue that such beliefs shape Catholic identity for apocalyptic Catholics.